2021
DOI: 10.1177/1558866121995169
|View full text |Cite
|
Sign up to set email alerts
|

Collegiate Sport Club Athletes’ Psychological Well-Being and Perceptions of Their Team Climate

Abstract: The purpose of this study was to consider how the Positive Coaching Alliance (PCA) Triple-Impact Competitor (TIC) workshop could be used to help create a positive climate for recreational sport club participants, and to examine how perceptions of a positive team climate related to indices of psychological well-being among sport club athletes. At the beginning of their season, sport club leaders completed the PCA TIC workshop. Following the conclusion of the spring season, we invited all sport club participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Self-compassion would also help performers overcome feelings of stigmatization over their vulnerabilities by allowing them to seek help. The research reviewed showed that more self-compassionate athletes reported seeking the help they thought necessary more frequently than their less self-compassionate peers ( Scott et al, 2021 ). Future studies should include more representative samples from a wider range of performers (i.e., athletes, dancers, and musicians) to investigate the potential effects of different performance cultures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Self-compassion would also help performers overcome feelings of stigmatization over their vulnerabilities by allowing them to seek help. The research reviewed showed that more self-compassionate athletes reported seeking the help they thought necessary more frequently than their less self-compassionate peers ( Scott et al, 2021 ). Future studies should include more representative samples from a wider range of performers (i.e., athletes, dancers, and musicians) to investigate the potential effects of different performance cultures.…”
Section: Discussionmentioning
confidence: 99%
“…The development of self-compassion has also proven to be an important driver in the search for psychological help ( Heath et al, 2017 ) in the general population. Indeed, it could be hypothesized that developing a compassionate and caring environment around performers would help them to develop self-compassion which, as shown in various research studies, improves well-being and performance ( Jeon et al, 2016 ; Frentz et al, 2020 ; Scott et al, 2021 ). It could also lead to performers being more open to seeking psychological help when needed ( Adam et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fry and Moore (2019) completed a review of the sport psychology literature, highlighting how participants’ perceptions of a CTIC are related to numerous positive outcomes, including enjoyment, higher self-esteem, and psychological wellbeing. On college recreational sport club teams, Scott et al (2021) found that athletes’ perceptions of a CTIC were significantly and positively related to their overall hope, happiness, and self-kindness in life. Brown and Fry (2015) created a 90-minute intervention for recreation staff that provided strategies for creating a CTIC.…”
mentioning
confidence: 98%